Food Storage Strategies and Food Quality at Samalona Signature Restaurant, Nusa Dua Bali - Firmansyah, Rinno Rahmat; Wiantara, I Gusti Nyoman; Nainggolan, Pondang Polikarpus (LPPM Universitas Dhyana Pura, 2026)
Food storage is a critical operational control in restaurant kitchens because it determines ingredient freshness, food safety, product consistency, and the level of food waste. This study aims to analyze food storage strategies and their implications for food quality at Samalona Signature Restaurant, Nusa Dua Bali. The study used a descriptive qualitative design. Data were collected through direct observation, semi-structured interviews with the Executive Chef, and documentation of internal food waste records from January to November 2025. The analysis followed three stages: data reduction, thematic data display, and conclusion drawing. The findings show that the restaurant has implemented several basic storage practices, including dry, chilled, and frozen storage, stock rotation using FIFO/FEFO principles, and periodic monitoring by kitchen management. However, the implementation remains inconsistent in terms of zoning, date labelling, temperature documentation, and separation of food ingredients with different physical and microbiological characteristics. Internal records show 324 kg of food waste during the observed period, with the highest monthly waste recorded in January (50 kg), April (45 kg), and September (41 kg). These results indicate that food storage practices are not only an inventory issue but also a strategic determinant of food quality. More disciplined zoning, routine temperature logs, clear labelling, daily stock cards, and staff training are recommended to improve freshness, reduce spoilage, prevent cross-contamination, and maintain the sensory quality of dishes served to guests.